Mapping the uncertainty in modulus reduction and damping curves onto the uncertainty of site amplification functions - Bahrampouri,M; Rodriguez-Marek,A; Bommer,JJ (Soil Dynamics and Earthquake Engineering, 2019)
Probabilistic seismic hazard analysis often requires the use of site response analyses to calculate site amplification factors (AFs) that capture the effects of near-surface layers. The site response analyses must also be conducted in a probabilistic framework to quantify the variability in AFs resulting from variation in the rock input motions and uncertainty in the dynamic properties of the soil profile, including uncertainty in the shear-wave velocity and in the nonlinear behavior of the soil. In equivalent linear analyses, the latter is captured through modulus reduction and damping curves (MRD). The joint randomization of shear-wave velocity and MRD curves can result in large computational costs. The objective of this paper is to propose a procedure to separately calculate the contribution of uncertainty in the MRD curves to the total uncertainty in the AFs for a site. This procedure is illustrated in an application for a seismic hazard and risk assessment of the Groningen gas field in the Netherlands. The results show that the effect of uncertainty in MRD curves on the uncertainty in the AFs is highly dependent on the soil profile. This effect can be significant for soft soils and strong input motions. Results also indicate that the effects of MRD uncertainty can be correlated to elastic site properties.